Rasgos de personalidad y consumo de alcohol en músicos profesionales de la ciudad de Loja, periodo 2019 - Sánchez Castillo, Jefrey Dánelber (2020)
Alcohol consumption has been a problem worldwide, continental, national and local for many years, initiating problems of labor, family and personal nature, as well as psychological and biological ailments. The objective of this study is to determine the relationship between personality traits and alcohol consumption. For which a descriptive-correlational design with cross-section was made, in which 82 professional musicians from the Symphony Orchestra of Loja and the Municipal Symphony Orchestra of Loja participated, which were selected by cluster sampling, not probabilistic and intentional. The instruments used were: The Five-Factor Reduced Personality Inventory (NEO-FFI) and the Alcohol Consumption Disorders Identification Test (AUDIT). The results suggest that the majority of the population under study does not present alcohol-related problems, physical or psychological problems with drinking, or probable alcohol dependence. A higher percentage was identified with the personality trait of neuroticism at a medium high level, followed by a medium low level in the personality trait of extraversion and kindness. In addition, there is a significant correlation between the personality trait of neuroticism and the variable physical and psychological problems with drinking and probable dependence on problematic alcohol consumption. Keywords: personality, personality traits, alcohol, alcohol consumption, professional musicians, symphony orchestra.